Conductivity, thermal behaviour and ftir studies on different modified natural rubbers / Nur Atiqah Hamidun - Hamidun, Nur Atiqah (Faculty of Applied Sciences, 2009)
Epoxidized natural rubbers (ENR-25 and ENR-50), methylated grafted natural rubbers (MG-30 and MG-49) and deproteinized natural rubber (DPNR) doped with 0 - 30 wt % of LiClO4 were prepared by solution casting technique. Thermal stability ( d T ) and glass transition temperature ( g T ) of all the rubber samples were investigated by Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC), respectively. Quantities d T show that ENR-25 and ENR-50 are thermally more stable than that of DPNR, MG-30 and MG-49. The Tg values of all the rubber samples show no significant variation with ascending salt content after 5 wt % of LiClO4 added. Ionic conductivity ( studied by impedance spectroscopy show that MG-49 and ENR-25 exhibit higher  values of 8.810-8 and 9.510-8 S cm-1 than MG-30 and ENR-50, respectively. ATR-FTIR was applied to examine the ion-dipole interactions between the LiClO4 salt and the rubber samples. It is observed that the Li+ ions preferentially coordinated to the epoxy oxygen of the ENR. For MG-30 and MG-49, the Li+ ions are mainly coordinated to the C-O and the C=O of the ester groups.